EFFECT OF TREHALOSE AND AMYLASE ON ECONOMIC CHARACTERS OF TASAR SILKWORM, ANTHERAEA MYLITTA D (SUKINDA ECORACE) IN EX-SITU CONDITIONS - SREENIVAS.M; SHAMITHA.G (International Journal of Pharma and Bio Sciences, 2015)
The tasar silkworm Antheraea mylitta D., a wild sericigenous and polyphagous insect of India, basically feeding on Terminalia sp, is a trivoltine, tropical variety. In the present study, biochemical and economic parameters of Tasar silkworm, (Sukinda ecorace) are analysed. It was observed that a lowest capacity of silk yield in sukinda suggests for a more viable method of crop stabilisation as a cause of concern though Daba and Sukinda ecoraces are mostly commercially applied for cocoon production.